Juxtaposed and superimposed paleomagnetic primary and secondary components from the folded middle carboniferous sediments in the Reggane Basin (Saharan craton, Algeria) - (:unkn) unknown (My University, 2001)
A paleomagnetic study was carried out on the Middle Carboniferous sediments of the eastern margin of the Reggane Basin of Algeria. Seven sites (108 samples) in the Lower Serpukhovian and 11 sites (129 samples) in the Upper Serpukhovian, Bashkirian and Lower Moscovian levels were investigated. Besides a common, but generally limited, viscous remanent magnetization (component A) and a recent chemical remanent magnetization of reversed polarity (A‧), two main components were identified: one of these (component B), is characterized by a negative fold test and has been identified as a Lower Jurassic remagnetization. The associated paleomagnetic pole obtained in the seven zones by combining characteristic remanent magnetization directions (ChRM) and great circles (λ=71.1°N, ϕ=251.4°E, A95=3.8°, K=254) lies in the vicinity of the NW African poles of similar ages. The second (component C) displays both normal and reversed polarities. Also determined by the combination of ChRM or stable end points and remagnetization circles, it yields a positive fold test which constrains the magnetization acquisition time and a positive reversal test which argues in favor of a ;non-composite; nature of the component C. The normal polarities observed in the Lower Serpukhovian levels represent the latest normal event observed in Africa before the Kiaman superchron. The paleomagnetic South pole calculated from 10 sites (n=64 data) gathered in four large areas (λ=26.5°S, ϕ=44.7°E, A95=4.7°, K=383) is the first African Carboniferous pole founded on both positive reversal and fold tests. It lies only slightly apart from other Middle Carboniferous poles previously published for the northern part of Africa where no intraformational test were available to constrain the magnetization age.
Keywords: African Research